A Complication of Percutaneous Sclerotherapy for Congenital Pulmonary Airway Malformation: Intravascular Injection and Cardiac Necrosis. (2nd November 2017) - H. Chon, Andrew; Takeda, Moe R.; Felix, Juan C.; Chmait, Ramen H.
ABSTRACT: Introduction : A congenital pulmonary airway malformation (CPAM) type III may become large enough to cause hydrops fetalis. In such circumstances, the fetus can be treated with open fetal resection, maternal betamethasone administration, or percutaneous sclerotherapy. Case report : A 24 week gestation fetus with a CPAM type III was treated by percutaneous sclerotherapy using ethanolamine oleate (EO). The EO inadvertently entered the left atrium and ventricle with subsequent fetal bradycardia and demise. Autopsy revealed myocardial necrosis. Conclusion : Percutaneous sclerotherapy has been previously described in the literature for the treatment of microcystic CPAMs with secondary hydrops. This is the first reported case of an adverse event after fetal sclerotherapy.